Chemotherapy Immunophenoprofiles in Non‐Small‐Cell Lung Cancer by Personalized Membrane Proteomics. Issue 2 (19th January 2018) - Putri, Denise Utami; Feng, Po‐Hao; Hsu, Yuu‐Hueih; Lee, Kang‐Yun; Jiang, Feng‐Wen; Kuo, Lu‐Wei; Chen, Yu‐Ju; Han, Chia‐Li
Abstract: Objectives: No study has addressed how the immune status at the molecular level is affected by first‐line pemetrexed and cisplatin (PEM–CIS) combination therapy in patients with non‐small‐cell lung cancer (NSCLC). Thus, we aimed to identify the immune status from membrane proteome alterations in patients with NSCLC upon PEM–CIS treatment. Methods: The paired peripheral blood mononuclear cells (PBMCs) were collected from four patients with lung adenocarcinoma before and after the first regimen of PEM–CIS treatment and applied quantitative membrane proteomics analysis. Result: In the personalized PBMC membrane proteome profiles, 2424 proteins were identified as displaying patient‐specific responsive patterns. We discovered an elevated neutrophil activity and a more suppressive T‐cell phenotype with the downregulation of cytotoxic T lymphocyte antigen 4 degradation and the upregulation of type 2 T‐helper and T‐regulatory cells in the patient with the highest progression‐free survival (PFS) of 14.5 months. Patients with a PFS of 2 months showed higher expressions of T‐cell subsets, MHC class II pathways, and T‐cell receptor signaling, which indicated an activated immune status. Conclusion and Clinical Relevance: Without the additional isolation of specific immune cell populations, our study demonstrated that PEM–CIS chemotherapy altered patients' immune system in terms of neutrophils, T cells, and antigen presentation pathways.